Simplified technique for constitutive analysis of SFRC - Meskenas, Adas; Gribniak, Viktor; Kaklauskas, Gintaris; Arnautov, Aleksandr K.; Rimkus, Arvydas (Journal of Civil Engineering and Management, 2014)
Steel fibre reinforced concrete (SFRC) has become widespread material in areas such as underground shotcrete structures and industrial floors. However, due to the absence of material models of SFRC reliable for numerical analysis, application fields of this material are still limited. Due to interaction of concrete with fibres, a cracked section is able to carry a significant portion of tensile stresses, called the residual stresses. In present practices, residual stresses used for strength, deflection and crack width analysis are quantified by means of standard tests. However, interpretation of these test results is based on approximation using empirically deduced relationships, adequacy of which might be insufficient for an advanced numerical analysis. Based on general principles of material mechanics, this paper proposes a methodology for determination of residual stress-crack opening relationships using experimental data of three-point bending tests. To verify the constitutive analysis results, a numerical modelling is utilised employing a nonlinear finite element analysis program ATENA. Simulated load-crack width relationships and moment-curvature diagrams were compared with the experimental data by validating adequacy of the derived constitutive models.